Effect Soursop (Annona muricata L.) Leaf Aqueous Extract (SLAE) on Remodeling of Ventricle Heart Tissue in Obesity Rats Model - Hafidh Nur Haq; Aris Rosidah; Dini Sri Damayanti (Future Science)
A high-fat and high-fructose diet can lead to obesity which contributes to an increased risk of heart failure complications. Soursop leaves are known to have the potential of antioxidant, but research about the effects of soursop leaf on complications of heart failure has never been studied. This study evaluated whether soursop leaf aqueous extract can inhibit the total of cardiomyocyte necrosis, cardiomyocyte diameter, and density of cardiac collagen in obese rats. The heart organs of obese rats that have been paraffin, which randomly divided into normal group, obesity group, and soursop leaf aqueous extract (SLAE) group with dose I (100 mg/kgbw), II (200 mg/kgbw), and III (400 mg/kgbw) (n=6 rats). The rats were induced by high-fat high-fructose and SLI diets for 10 weeks. The number of necrosis and diameter cardiomyocytes were measured by using Hematoxylin Eosin staining, while the density of cardiac collagen was measured by Masson's Trichrome staining and then observed with a trinocular and dot side microscope at 200x and 400x magnification. Statistical analysis using One Way ANOVA and continued by LSD test. We found that group SLAE with doses I, II, and III significantly reduced the number of cardiomyocyte necrosis and cardiac collagen density compared to the obesity group. The SLI group with doses II and III significantly reduced the diameter of cardiomyocytes compared to the obesity group, while the SLAE group with the dose I was unable to reduce the diameter of cardiomyocytes. In conclusion, Soursop leaf aqueous extract can inhibit the increase of cardiac collagen density, number necrosis and diameter cardiomyocyte.